The effectiveness of monitoring as a necessary condition for the adoption of correct decisions on the security оf technosphere - V. M. Mikhailov (Российский технологический журнал)
This article discusses the issues of ensuring the effectiveness of monitoring for correct estimates of parameter manifestations (start time, intensity and severity) of catastrophic natural (earthquakes, floods and others) and man-made (water and air pollution) processes. Organizational structure of monitoring with reasonable time and address of the measurement mode taking into account the main features and stages of forming controlled natural and technogenic processes should ensure the acquisition of data needed for further calculations of the start time of earthquakes, territorial distribution and levels of water or air pollution, etc. Besides, the article outlines requirements for the relevant qualification of engaged staff capable of correctly interpreting the results of monitoring measurements and performing the necessary calculation of numerous parameters, for example, in the case of pollution evaluation. As a result, all this allows to ensure the compliance of obtained assessments with the real condition of monitored object, which is the basis for informed decisions on a set of actions to further ensure technosphere security. Along with this, the proposed monitoring approach allows to optimize the measuring base in order to achieve the necessary efficiency in assessing the status of controlled objects and the layout of the base in terms of the characteristics of buildings and their intrinsic properties, as well as the specificity of technogenic impact and natural processes on technosphere objects.